PERANCANGAN APLIKASI SIKLUS AKUNTANSI BERBASIS EXCEL FOR ACCOUNTING PADA UMKM WARUNG AGIN PABUARAN MEKAR - Ariyadi, Agin Putra; Yasin, Muhammad; Octaviany, Featy (JURNAL LENTERA AKUNTANSI, 2025)
observation that aims to answer the problem formulation about how the conditions of recording financial transactions that have been running in MSMEs, how to design the accounting system finance using Excel For Accounting, and How is the process of preparing financial statements by applying Excel For Accounting. In this study, the authors used the library study writing methodology and field studies. Data collection through observation and interviews. The result of this study is that the authors found that these MSMEs only kept simple records in the form of transaction records every day. So that MSMEs Warung Agin Pabuaran Mekar needs help in designing structured records and designing financial reports using Excel For Accounting so that it can make it easier for owners to project and calculate numbers related to business operations and minimize the risk of errors that may occur. so that the financial statements are properly structured. And can help in making decisions for future business developments.